Foraging Behavior of Praon volucre (Hymenoptera: Braconidae) a Parasitoid of Sitobion avenae (Hemiptera: Aphididae) on Wheat - Afrooz Farhad; Ali Asghar Talebi; Yaghoub Fathipour (Psyche: A Journal of Entomology)
Host stage preference, functional response and, mutual interference of Praon volucre (Haliday) (Hym.: Braconidae) parasitizing the grain aphid, Sitobion avenae (Fabricius) (Hem.: Aphididae), were investigated under laboratory conditions. Host stage preference was evaluated at 25±1°C, 60±5% relative humidity and a photoperiod of 16:8 h (L : D), under choice and no-choice tests. Functional response was done under five constant temperatures (10, 15, 20, 25, and 30°C), 60±5% relative humidity and a photoperiod of 16:8 h. (L : D). Praon volucre parasitized all nymphal instars and adults of the grain aphid but strongly preferred to oviposit into second-instar nymphs in both choice and no-choice conditions. Results of logistic regression revealed a type II functional response for all temperatures tested. The handling time (Th) and searching efficiency (a) were estimated using the Rogers equation. The maximum estimate of searching efficiency occurred at 15°C and 20°C (both 0.05±0.01 h-1) and decreased to 0.01±0.01 h-1 at 30±1°C. The minimum estimate of handling time was 1.02±0.11 h at 25°C and increased to 5.31±0.82 h at 30±1°C. The maximum rate of parasitism was 23.52 aphids/female/day at 25°C. With parasitoid density increasing from 1 to 8, the per capita searching efficiency decreased from 0.12 h-1 to 0.06 h-1. The results suggested that P. voluvre has the potential to be a biocontrol agent of S. avenae. However, evaluation of foraging behavior warrants further investigation under field conditions.